Implementasi Nilai-nilai Pendidikan Kewarganegaraan untuk Meningkatkan Kecakapan Citizenship Abad 21 di Madrasah Ibtidaiyah - Ulvi Laili; Imam Muslih (Tarunateach: Journal of Elementary School, 2025)
The principles of Civic Education play a crucial role in shaping students' character and equipping the younger generation with the necessary knowledge to navigate current and future societal challenges and interactions. This research seeks to explore and explain the core values of Civic Education, its practical application in enhancing 21st-century citizenship competencies, and the various factors that either support or hinder its implementation at MI Al-Ittihad. A qualitative method with a case study design was employed in this study. Data collection techniques included observation, interviews, and documentation, followed by analysis through data reduction, data display, and conclusion drawing. The findings indicate that Civic Education values extend beyond fostering awareness of citizens' rights and responsibilities, but also form superior character through religious, socio- cultural, physical-spiritual, and intelligence values (substantive, operational, innovative), social-cultural personal, social, and social-political personal. Its implementation is carried out through daily habituation, extracurricular activities, and school programs that support the improvement of student citizenship. The supporting factors include teacher support, curriculum, infrastructure, and a conducive school environment. The obstacles include obstacles in controlling the use of gadgets, the influence of the social environment, and sometimes there is an imbalance between learning materials and practices.